Ophthalmic Manifestations of Leukemia and Their Management - Chakroborty, Kripadhan; Hasan, Mohammad Mahbubul; Hasanuzzaman, Md; Sultana, Zakia; Khaleque, Sajed Abdul (Mugda Medical College Journal, 2024)
Patients with leukemia often have ophthalmic manifestations. These occur either from direct infiltrations of neoplastic cells or from indirect or secondary causes. Nearly all ocular structures can be affected by leukemia. Sometimes, ophthalmic involvement can be the first sign of disease relapse. This review article aims to highlight different ocular manifestations of leukemia along with treatment. It involves studying the available material in textbooks, printed and online journals. As there is high prevalence of ocular findings in leukemia, it can be a standard practice that all leukemic patients should have screening by ocular examination. Awareness of the clinical spectrum of leukemic infiltration of ocular region is essential for rapid diagnosis, prompt initiation of treatment and better outcome. If prompt diagnosis and treatment can be done, worsening of vision may be minimized or prevented. Mugda Med Coll J. 2024; 7(1): 36-41